Communicating martial arts knowledge: Conferring over a wealth of possibilities (Revista de Artes Marciales Asiáticas, 2017)
The 3rd Annual Martial Arts Studies Conference held at Cardiff University (11-13 July, 2017) was an eclectic collection of keynotes, papers, workshops, networking and social events. It connected PhD students, established professors and practitioner-instructors in university lecture rooms, public parks and music halls across three days of academic, social and physical activities. From historical studies of Chinese martial arts to the performance of Indian styles, it brought together scholars, practitioner-researchers and martial artists for a supportive, but also scholarly, gathering – one which was both thematically open but at the same united by an exploration of the communication of embodied research and knowledge. In sum, the conference demonstrated that martial arts studies, as a still young field, shows a wealth of promise, with emerging leaders, topics and debates that will stimulate future research, cross-continental collaboration and intercultural dialogue.